2023
DOI: 10.2106/jbjs.oa.22.00143
|View full text |Cite
|
Sign up to set email alerts
|

Residency Match Rates in Orthopaedic Surgery Based on Sex, Under-Represented in Medicine Status, and Degree Type

Abstract: Introduction: Orthopaedic surgery is well recognized as one of the most competitive and least diverse medical specialties. Despite efforts toward improving diversity, studies have shown that gender and racial/ethnic disparities continue to persist in orthopaedic graduate medical education. Therefore, we sought to identify the match rates of traditionally under-represented groups within orthopaedic surgery-female candidates, racial and ethnic minorities under-represented in medicine (URiM), and osteopathic phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…This study predicts that it will take approximately 16 years for female medical student application rates in orthopaedic surgery to achieve a previously defined rate of gender parity in orthopaedic surgery. Although this study does not directly address match rates, a recent study suggests that female applicants match into orthopaedics concordant with their application rates 26 . Further studies are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This study predicts that it will take approximately 16 years for female medical student application rates in orthopaedic surgery to achieve a previously defined rate of gender parity in orthopaedic surgery. Although this study does not directly address match rates, a recent study suggests that female applicants match into orthopaedics concordant with their application rates 26 . Further studies are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study investigating match rates of traditionally underrepresented groups in orthopaedic surgery, including females, found that female applicants applying to orthopaedic surgeries successfully match at a rate reflective of their application rates 26 . This thereby suggests that an increasing number of female applicants will likely lead to a predictable increase in female orthopaedic surgery residents and ultimately practicing physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Residency programs are recognizing the importance of recruiting diverse classes. 27,28 As there are only a finite number of applicants to PM&R each year, supporting recruitment practices that promote increasing diversity can allow for better maximization of the available talent pool. It is important to recognize that there are many different subtypes of diversity.…”
Section: Discussionmentioning
confidence: 99%
“…29 In the field of orthopedic surgery, often identified as one of the least diverse medical specialties, increasing recruitment of women and minority groups has been an area of focus for over 20 yrs. 30 Despite this, match rates of female and URiM candidates continue to be at or below their application rates, 28,30 leading to continued disparities when compared with the makeup of the general population. Program directors hold important leadership roles in the recruitment process and, when surveyed, can provide unique perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…From 2014 to 2019, 37 orthopaedic residency programs had no women trainees [19]. While the percentage of women entering orthopaedic surgery residency increased from 20.1% to 36.4% from 2001 to 2022, and application and match rates for women appear comparable to those of men [21], this growth remains less than other surgical subspecialties [20], and orthopaedics continues to consistently have the lowest representation of women among surgical subspecialties [8], at 18.3% by most-recent ACGME data [1]. Students from underrepresented racial and ethnic groups are less likely to match into orthopaedics [16].…”
mentioning
confidence: 99%